PENYELESAIAN KREDIT BERMASALAH DALAM PERJANJIAN KREDIT DENGAN JAMINAN HAK TANGGUNGAN DI BPR KARYA SARI SEDANA DENPASAR - Agus Wirajaya, I Gede Komang; Puspawati, I Gusti Ayu; Mudana, I Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 03, Juni 2014)
People who do not have enough funds to start the business activities and to acquire goods usually will try to borrow money through bank credit, both productive and consumer credit loans. Productive loans are loans given to businesses that produce goods and services, while consumer loans are loans given to the general public as individuals to make ends meet. The goal is to be able to describe the non-performing loans with mortgage guarantees, as well as to find out the resolution of problem loans in the loan agreement with a banking institution mortgage guarantees. Research carried out by the fact that there are in the field of settlement of non-performing loans in the loan  agreement with collateral mortgage. Settlement of bad loans tied to mortgage the bank before the bank doing the auction, the bank will make efforts to rescue the credit through credit prior to the completion of the restructuring of bad loans.
Keywords: credit, business, money, bank